Copper Plating on Glass Using a Solution Processed Copper-Titanium Oxide Catalytic Adhesion Layer. Issue 5 (20th February 2016) - Okabe, Kyohei; Kagami, Takahiro; Horiuchi, Yoshio; Takai, Osamu; Honma, Hideo; Cordonier, Christopher E. J.
Abstract : A method for copper deposition on glass and ceramics was investigated by direct plating on 20–30 nm thick copper inclusive titanium oxide films formed on the substrate surface. The copper inclusive titanium oxide film functioned as an adhesion layer and as a catalyst for autocatalytic copper deposition. Copper inclusive titanium oxide films were formed by pyrolysis of solution deposited 1-hydroxy phenyl ketone titanium-copper complex films. After deposition of electroless copper seed layers, 15–20 μm thick electrolytic copper films were formed, where upon thermal treatment up to 0.5 kN/m adhesion strength was attained on borosilicate glass. This process enabled electroless copper plating without the use of palladium as a catalyst on non-roughened smooth glass or ceramic substrate surfaces. The copper-titanium oxide adhesion layers were characterized and cross-sectional transmission electron microscopy illustrated the adhesion mechanism and catalyst structure.